Analisis hukum kebijakan moneter dalam mengatasi krisis ekonomi global: Problematika dan implementasi - Pakhriah, Ummi (Maliki Interdisciplinary Journal, 2025)
A legal analysis of the government’s economic policy in the face of the global economic crisis shows the complex relationship between the need for flexibility in emergency policy-making and the principles of the rule of law. The research explains that the legal system in Indonesia often faces a dilemma, between giving sufficient discretionary power to the executive and ensuring the limits set by the constitution. One of the main problems that arise is the existence of lacunae in the ordinary law which encourages the government to use emergency legal instruments such as Perppu, which can lead to legal uncertainty. In addition, there is a conflict between the efficiency of emergency policies and the principle of legality, as well as the risk of abuse of executive power in the absence of adequate checks and balances mechanisms. These issues indicate the need for a more specific legal framework to regulate protocols in situations of national crisis, the inclusion of principles of fairness in emergency regulations, and increased parliamentary oversight of emergency fiscal and monetary policies. Therefore, this study recommends a hybrid legal model that can combine administrative flexibility with substantial rule of law principles, so that crisis policies remain accountable and responsive to global changes.